Labour Process Theory: From Taylorism to Algorithmic Management - Ilya Konovalov (Journal of Economic Sociology, 2023)
This article provides an overview of the conceptual development of Labor Process Theory, from Braverman’s classic work to contemporary research dedicated to platform work. The article examines the theory’s conceptual framework: the concept of labor and its indeterminacy, the fundamental structural contradiction of the antagonism between capital and labor, and technology as an expression of this contradiction. The article discusses the four main branches of the labor process theory: the control/resistance paradigm, the theory of consent and hegemony, a postmodern approach, and paleo-Marxism. By doing so, it maps the development of the theory and its concepts. In addition to providing a general overview, this article offers an original interpretation of the labor process theory, which emphasizes the significance of knowledge in the labour process. This interpretation clarifies why the theory has become relevant again in the analysis of platform work and why it is potentially the most adequate framework for such analysis. The article argues that control over labor in the labour process theory can be understood in two ways: as control over specific technical work operations or as control over knowledge within the production process and access to the totality of production. The article looks at studies of platform work that use labour process theory and focus on information asymmetry as a way of control. It demonstrates that the relationship between classic labor process theory and platform economy research could be based on this second interpretation. We argue that the labor process theory can become the foundation that conceptually unites research of various types of platform work and allows for the description of elements of platform work outside the framework of platform employment.